Sex-Gender Dissidence and Political Identity inKleinstadtnovelle[Small-Town Story] by Ronald Schernikau (2018)
Kleinstadtnovelle , by Ronald Schernikau, was published in 1980, a turning point year between the Schulewebegung decade in Germany and a growing transnational normalization of gayness that would have as a result the perspective of Queer Studies and queer militancy in the United States. This article discusses the gay-lesbian liberation movements of the 1970s decade in Germany, in order to analyze how, in Schernikau’s literary text, it can be seen that, new systems for the production and intelligibility of humanness were starting to opérate at the beginning of the 1980s. Within these new systems, the log- ic of shame and discretion seems still to be at work, together with the normalization of homosexuality, following the parameters of normal heterosexual life. This was a time when sexuality was starting to be an issue for debate in the media, which became a new type of power/knowledge for this reason. In this context, identity became a strong weapon of political struggle.